Identification of the unique and common genes for asthma and chronic obstructive pulmonary disease: a case-control study in Kazakhstan (International Journal of Biology and Chemistry, 2018)
Asthma and chronic obstructive pulmonary disease (COPD) are lung inflammatory diseases characterized by bronchial obstruction, which is often the cause of difficulties in conducting differential diagnosis between them. They belong to the polygenic diseases, which arise in a result of the geneenvironment interactions. Identification of the unique and common genes for these diseases facilitates understanding of their complicated pathogenesis, and provides possible markers for their diagnosis and treatment. The aim of this study was to investigate the association of two single-nucleotide polymorphisms (-1082 A/G IL-10 and His161Arg IL17F) with asthma and COPD in Kazakh population. The study groups consisted of 72 COPD patients, 71 asthmatics and 70 control individuals. Genotyping was performed on purified DNA using real-time polymerase chain reaction with specific primers and probes. Results revealed that the G allele and GG genotype frequencies of -1082 A/G IL-10 polymorphism were significantly different between the COPD patients and the controls. Furthermore, the G allele and GG genotype of His161Arg IL-17F were significantly more common in the COPD patients than among the control individuals (p